The effect on performance of detraining during Covid-19 pandemic period in amateur soccer players - Yüksel, Mehmet Fatih; Koç, Ömer Fatih; Işık, Bülent; Erdağı, Kenan (Progress in Nutrition, 2022)
Abstract: Background and aim: Covid-19 pandemic has dramatically affected football, one of the most popular sports in the world, and significantly changed the competitive football sphere. This study was conducted to examine the effects of the suspensions and isolation process applied in leagues due to Covid-19 on the performance levels of amateur football players. Methods: Twenty male amateur football players (19.05±1.3 years) participated in the study as volunteers. Certain physical tests were applied to examine participants’ performance levels. The detraining period was 80 days. Pre-testing started in March 2020 when the restrictions first introduced in Turkey as the post-test process was initialized in the first week of June after normalization signals. Results: Results showed that there are statistically significant variances in the parameters of body weight, body mass index, sit-and-reach, hand grip strength, medicine ball throw, 30-m speed, Illinois agility, 30-sec sit-ups, 30-sec push-ups, counter movement jump, peak power, Yo-yo IR-Level 1 and V̇O2max (p<0.05). Conclusions: It was concluded that the performance levels of amateur football players deteriorated significantly during the detraining period due to the pandemic.